Climate Risk Management in Agricultural Extension (CRMAE) Multistakeholder Curriculum Consultative Workshop in Kenya - Grossi, Amanda; Dinku, Tufa; Hansen, James (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
A three-day multistakeholder consultative workshop was convened from April 12 to April 14, 2023, in Nairobi, Kenya by the International Livestock Research Institute (ILRI), in close collaboration with the Kenya Meteorological Department (KMD), the Kenya Agricultural and Livestock Research Organization (KALRO), and the International Research Institute for Climate and Society (IRI) of the Columbia Climate School. The workshop, which was organized as part of the World Bank’s Accelerating the Impacts of CGIAR Climate Research for Africa (AICCRA) project, brought together 8 participants representing Kenya’s agricultural extension and advisory service (EAS) providers and institutions which inform Kenya’s EAS providers to co-design a curriculum to support climate risk management in agricultural extension.